2009
DOI: 10.1002/pfi.20042
|View full text |Cite
|
Sign up to set email alerts
|

Using Six Sigma for performance improvement in business curriculum: A case study

Abstract: During the last few decades, a number of quality improvement methodologies have been used by organizations. This article provides a brief review of the quality improvement literature related to academia and a case study using Six Sigma methodology to analyze students' performance in a standardized examination. We found Six Sigma to be an effective tool for curriculum improvement and team building. The challenges and benefits of using Six Sigma are discussed.DURING THE PAST FEW DECADES, a number of quality impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
7
0
4
Order By: Relevance
“…Although previous studies have tended to frame LSS applications in higher education from an institutional perspective (Jenicke et al 2008;Kukreja et al, 2009 andYu andUeng, 2012), our research finds that individual faculty can also benefit from using the DMAIC procedure to help inform and guide their research initiatives. Adopting a project to project isomorphic perspective (Miterev, M., Engwall, M., & Jerbrant, A.…”
Section: Carl F Berardinellimentioning
confidence: 82%
See 1 more Smart Citation
“…Although previous studies have tended to frame LSS applications in higher education from an institutional perspective (Jenicke et al 2008;Kukreja et al, 2009 andYu andUeng, 2012), our research finds that individual faculty can also benefit from using the DMAIC procedure to help inform and guide their research initiatives. Adopting a project to project isomorphic perspective (Miterev, M., Engwall, M., & Jerbrant, A.…”
Section: Carl F Berardinellimentioning
confidence: 82%
“…Common issues include the necessity of sponsorship and support by senior leadership, difficulty measuring the exact nature of the educational product, necessity of dealing with long measurement time periods common in higher education assessment protocols, the service nature of education and the overall misalignment of faculty reward systems. Nevertheless, there have been some encouraging adoptions and case studies reported in the higher education literature (Al-Kuwaiti and Vijay, 2015;Holmes, Jenicke and Hempel, 2015;Kukreja, Ricks, Jr. and Meyer, 2009;Pavlovic et al, 2014;Yu and Ueng, 2012).…”
Section: Lean Six-sigma and Higher Educationmentioning
confidence: 99%
“…En cuanto al mejoramiento de procesos académicos se encuentra el caso de la Universidad de Texas en el que se utilizaron equipos de estudiantes y ayudas tecnológicas para el proceso de aprobación del currículo y de curso con el fin de reducir el tiempo de ciclo, logrando una reducción del 78.9% [27]. Otro ejemplo en mejora de procesos académicos lo constituye el caso aplicado por Kukreja et al [28] en el cual implementaron Six Sigma para mejorar el curriculo del programa de Administración de Empresas con el fin de obtener la acreditación del programa. A pesar de encontrar grandes ventajas en su implementación, el autor observó que se requiere y se consume un tiempo importante en la implementación de esta metodología, especialmente en la obtención de los datos.…”
Section: Six Sigma En Iesunclassified
“…Resulta interesante nombrar el proyecto que se ejecutó en una IES no especificada para reducir la deserción estudiantil utilizando la metodología Lean Six Sigma con la estructura DMAIC, se demostró que resulta viable para este tipo de problemas aplicar esta metodología, sin embargo, al ser un primer proyecto de este tipo se presentan barreras importantes por superar [51]. [53], [54], [18], [55], [48], [20], [56], [38], [13], [57], [58], [25], [28], [14], [40], [59], [47], [50], [60], [61], [62] 21 2 Mejorar el sistema de calidad y acreditación de las IES [54], [9], [48], [63], [64], [56], [38], [10], [57], [26], [59], [52], [47], [65], [61], [62] 16…”
Section: Lean Six Sigma En Iesunclassified
See 1 more Smart Citation